Examining Unlock Journaling with Diaries and Reminders for In Situ Self-Report in Health and Wellness - Zhang, Xiaoyi; Pina, Laura R; Fogarty, James (Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
In situ self-report is widely used in human-computer interaction, ubiquitous computing, and for assessment and intervention in health and wellness. Unfortunately, it remains limited by high burdens. We examine as an alternative. Specifically, we build upon recent work to introduce single-slide unlock journaling gestures appropriate for health and wellness measures. We then present the first field study comparing unlock journaling with traditional diaries and notification-based reminders in self-report of health and wellness measures. We find unlock journaling is less than reminders, dramatically improves of journaling, and can provide equal or better . Where appropriate to broader design needs, unlock journaling is thus an overall promising method for in situ self-report.